2021
DOI: 10.1007/s11910-021-01112-3
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in Pediatric Headache: A Review and Practical Implementation

Abstract: Purpose of Review The purpose of this review was to summarize the current literature about telemedicine in pediatric headache and to provide practical guidance for its implementation. Recent Findings There are few studies dedicated to telemedicine in pediatric headache, and existing studies are small. Patients and families report high levels of satisfaction with telemedicine, and most are willing to continue telemedicine visits in the future. Telemedicine demonstrated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Patient preferences for use of digital technologies to promote headache management indicate a need for health‐care providers to consider recommending digital tools that may benefit patients in the context of clinical care 25,27–29 . Despite the need for larger RCTs and development testing of culturally informed digital headache tools, the present literature suggests that self‐directed digital interventions and combination digital and in‐person interventions are promising.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Patient preferences for use of digital technologies to promote headache management indicate a need for health‐care providers to consider recommending digital tools that may benefit patients in the context of clinical care 25,27–29 . Despite the need for larger RCTs and development testing of culturally informed digital headache tools, the present literature suggests that self‐directed digital interventions and combination digital and in‐person interventions are promising.…”
Section: Discussionmentioning
confidence: 90%
“…25,[27][28][29] Despite the need for larger RCTs and development testing of culturally informed digital headache tools, the present literature suggests that self-directed digital interventions and combination digital and in-person interventions are promising. Patients may benefit from a referral for headache management interventions that combine digital technologies with health-care provider interactions or recommendations for self-directed digital headache interventions, which may be a more feasible approach in busy clinic settings.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Inability to carry out the focused physical examination which is especially important for children below 2 years of age 87,89,90,93 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a recent narrative review pointed out the efficacy of behavioral therapy for migraine patients administered through electronic health (e-health–telecommunication-based health). On the other side, the same review showed the absence of specific mobile app (m-health) to provide these therapies [ 29 ]. This novel strategy could be incorporated into the multidisciplinary approach to migraineurs, since it may support and engage patients between outpatient visits and encourage them to play a proactive role in the management of their pain.…”
Section: Tele-rehabilitation Approachesmentioning
confidence: 99%